Regularidades Discursivas em uma Coleção Didática de Biologia: O Ensino de Genética em sua Relação “Forma-Conteúdo” - Lopo Montalvão Neto, Alberto (Góndola, enseñanza y aprendizaje de las ciencias, 2023)
As discussed in research within the field of Biology Education, teaching Genetics is one of the most challenging tasks. This challenge arises not only due to the complexity and the abstract nature of its concepts but also because of the evolving characteristics of the field itself, which in recent years has seen significant advancements in molecular and (bio)technological techniques. Furthermore, it is the responsibility of formal education to codify this knowledge, which often circulates in various social contexts. Viewing the textbook as a significant resource for classroom practices conducted by teachers and students, and sometimes the only available material, we applied the French school of Discourse Analysis, influenced by Michel Pêcheux and primarily by the works of Eni Orlandi, to examine the discursive regularities in a biology textbook collection. Our objective was to comprehend how Genetic discourses are presented in a biology textbook collection and to understand the potential effects of sense production from the interaction between the text and the reader. As a result, we identified the alternation of three discursive typologies in sense production, which influence the ways in which content is presented in the textbook: everyday discourse, pedagogical discourse, and scientific discourse, with the latter being predominant. Additionally, the textbook often demonstrates characteristics of scientific neutrality and objectivity, along with the omission of socio-historical issues. Based on these results, we recognize the need to rethink Biology Education, moving away from authoritarian discourses and allowing room for alternative interpretations.